Quality of Reception with Risk Classification in Urgent and Emergency Services - , Wilhames Rodrigues da Silva Lima; , Ciane Regina Alves Barros; , Viviane Lima Nakamura; , Tiago de Lima Vieira Texeira; , Fábio Salgado da Silva; , Vitor Hugo Auzier Lima; , Thiago Augusto Ferreira dos Anjos; , Daniele Salgado de Sousa (Archives of Current Research International, 2023)
Introduction: The Reception with Risk Classification (ACCR) is an important tool for the Urgency and Emergency Services (SUE). Objective: To describe the frequency with which publications on ACCR have been occurring in the Brazilian scientific literature in recent years. Methods: A bibliographic study was carried out, with a qualitative approach, for literature review based on the use of the keyword "reception with risk classification", in the Regional Portal of the VHL using two databases. Results: We found 102 publications, 68 belonging to the LILACS database and 52 to the BDENF database, where 13 articles that were published between 2015 and 2019 were selected for full reading. It was noted that most of the publications focused on 2015, with emphasis on the southern region, in addition to most portraying the evaluation of the ACCR by the nurse. Conclusion: It is evident the need to expand research on quality in the ACCR both for the qualification of nursing professionals, as well as in the structural and human resources sectors, especially in the northern region of the country.